Evaluation of Biofertilizer Action in Pennisetum purpureum - de Varona Pérez, Ricardo; Vento Pérez, Mirna; Córrales Carriga, Ignacio; Chaveli Chávez, Pavel; López Labarta, Pedro (Agrisost ISSN 1025-0247, 2018)
Research was done on El Renacer Farm, at the 26 de Julio CCS (cooperative of credits and services) in the municipality of Camagüey, to evaluate the effect of biofertilizers on Pennisetum purpureum using a randomized block design with five treatments and five repetitions (liquid humus + phosphorine, liquid humus + azotobacter, liquid humus + phosphorine, liquid humus + phosphorine + azotobacter + essential elements, and a control treatment). Both azotobacter and phosphorine were applied to a 2 kg/ha dose in all the combinations, 1.5 l/ha of liquid humus, and 2 l/ha of essential elements, in the rainy and dry seasons. Samples were taken from the soil, and chemical analysis was performed to water for irrigation, according to the current standards. Evaluation was made of the number of stems per sapling, plant height, stem thickness, and yields. The best yields in the dry (20 t/ha) and rainy (23.6 t/ha) seasons were achieved with the liquid humus + phosphorine + azotobacter + essential elements.
Keywords: Fertilization; grass; biofertilizers; phosphorine; azotobacter; humus